COVID-19 policies and the arising of debate on twitter - Gozzo, Simona; D'Agata, Rosario (Frontiers in Sociology, 2023)
This study shows the results of disintermediation dynamics linked to the massive use of social networks, focusing on the communication structures related to the pandemic crisis. In this sense, social media constituted an important tool for the construction of identities, cultures and ideologies even as a reaction to ontological uncertainty resulting from closures. At the same time, this type of communication is a risk because it conveys out-of-control access to unreliable information and because it can lead to the absence of correct information, due to the reinforcing effect on cognitive fallacies linked to the process of algorithmic distortion of communication. On a technical level, at least three complex network structures evolving in different directions are identified, which emerged from three sequentially monitored keywords (#No-mask, #Covid-19, #Greenpass). Further considerations relate to the increasingly dense intertwining between online communication and the genesis of intermediary communities both stable and with evanescent and monothematic structures.